1987
DOI: 10.1073/pnas.84.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for the accumulation of insulin in nuclei of intact 3T3-L1 adipocytes by an insulin-receptor mediated process.

Abstract: Monomeric ferritin-labeled insulin (Fm-Ins), a biologically active, electron-dense marker of occupied insulin receptors, was used to characterize the internalization of insulin in 3T3-L1 adipocytes. Fm-Ins bound specifically to insulin receptors and was internalized in a time-and temperature-dependent manner. Fm-Ins was found in cytoplasmic vesicles within 5-10 min at 3rC and subsequently was observed in multivesicular bodies and Iysosomes. In addition, small amounts of Fm-Ins were associated with nuclei after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 42 publications
5
16
0
Order By: Relevance
“…Indeed, our 32D cells are hyperdiploid and our FDC-P1 cells are hypodiploid, and each cell line has several metacentric marker chromo- We also tested the possibility that internalized IL3 might be biologically active after release from the receptor. Several reports have appeared of nuclear localization after the internalization of polypeptide growth factors, including epidermal and nerve growth factors (34), basic fibroblast growth factor (4), platelet-derived growth factor (34,48), and insulin (33,43). IL3 need not be glycosylated to be biologically active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our 32D cells are hyperdiploid and our FDC-P1 cells are hypodiploid, and each cell line has several metacentric marker chromo- We also tested the possibility that internalized IL3 might be biologically active after release from the receptor. Several reports have appeared of nuclear localization after the internalization of polypeptide growth factors, including epidermal and nerve growth factors (34), basic fibroblast growth factor (4), platelet-derived growth factor (34,48), and insulin (33,43). IL3 need not be glycosylated to be biologically active.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems are compatible with a mechanism whereby receptor association and even signal transduction occur internally. More detailed analysis is available for platelet-derived growth factor/v-sis (19,24) (4,33,34,43,48). Internal oncogenelike effects have been described for acidic and basic fibroblast growth factor (4, 23); however, these repair-mediating growth factors do not possess signal sequences and stimulate proliferation in neighboring cells only after lysis of the damaged producer cells (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other reports suggest that the internalization of zymatic activities (Purrello et al, 1982), and mRNA release from nuclei (Schumm and Webb, 1983). We have demosntrated that insulin, but not its plasma membrane receptor, was translocated to and accumulated in the cell nucleus in several different cell types (Heyner et al, 1989;Smith and Jarett, 1987;Soler et al, 1989). Insulin in the nucleus was intact and tightly attached to the nuclear matrix .…”
Section: Introductionmentioning
confidence: 70%
“…We have demonstrated that internalized insulin was translocated to and accumulated in the nucleus of several different types of cells (Smith and Jarett, 1987;Heyner et al, 1989;Soler et al, 1989). It has been reported that other hormones or growth factors including epidermal growth factor (EGF), nerve growth factor (NGF), plateletderived growth factor (PDGF), fibroblast growth factor (aFGF) (reviewed by Burwen and Jones, 1987), insulin-like growth factor type I (IGF-I (Soler et al, 1990), and prolactin (Clevenger et al, 1991) are also translocated to and accumulated in the nucleus.…”
Section: Discussionmentioning
confidence: 99%